[Laiškas] / Čajevskis (Czajewski) Viktoras - Janui Karlovičiui. - (:unkn) unknown (My University, 1889)
1 laiškas dėl honoraro atsiuntimo už straipsnį, išspausdintą žurnale "Wisła".
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Čajevskis (Czajewski), Viktoras; Karłowicz, Jan Aleksander, 1836-1903